The Integrasi Endorphin Massage sebagai Holistic Care dalam Penurunan Kecemasan Kehamilan Trimester III - Murdiningsih Murdiningsih; Juwita Suryani; Sari Wahyuni (LPPM Hang Tuah Pekanbaru, 2022)
Anxiety in pregnant women tends to be experienced in the third trimester when going through the labor process. Holistic care, one of which endorphin massage is a non-pharmacological therapy to secrete endorphin hormones. This study aimed to determine the effect of endorphin massage on the anxiety level of third-trimester pregnant women at BPM Teti Herawati in 2020. This was a pre-experimental study with one group pre-test and post-test approach. The research sample was a pregnant woman in the third trimester who visited BPM Teti Herawati as many as 34 samples and had met the inclusion criteria with the accidental sampling method. The instruments used were the HARS scale and the SOP of Endorphin massage. The anxiety level of pregnant women in the third trimester before being given Endoprhin massage intervention has a median of 20,50 and minimum-maximum of 7-27. The anxiety level of pregnant women in the third trimester after being given Endoprhin massage intervention has a median of 11,50 and minimum-maximum of 4-19. Wilcoxon statistical test results obtained a p-value of 0,000 (p-value< 0,05), meaning that there is an influence of Endorphin massage intervention on anxiety in pregnant women in the third trimester. The conclusion, There is an effect of giving Endorphin massage on anxiety in pregnant women in the third trimester at BPM Teti Herawati 2020.